2005
DOI: 10.1074/jbc.m414331200
|View full text |Cite
|
Sign up to set email alerts
|

Compounds That Bind APP and Inhibit Aβ Processing in Vitro Suggest a Novel Approach to Alzheimer Disease Therapeutics

Abstract: Extracellular deposits of aggregated amyloid-␤ (A␤)peptides are a hallmark of Alzheimer disease; thus, inhibition of A␤ production and/or aggregation is an appealing strategy to thwart the onset and progression of this disease. The release of A␤ requires processing of the amyloid precursor protein (APP) by both ␤-and ␥-secretase. Using an assay that incorporates full-length recombinant APP as a substrate for ␤-secretase (BACE), we have identified a series of compounds that inhibit APP processing, but do not af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 54 publications
3
33
0
Order By: Relevance
“…BACE inhibitor IV completely eliminated BACE1 cleavage of the APP-C140 substrate, in contrast to Gleevec, which had no effect at all concentrations tested, thus again ruling out a direct inhibitory effect of Gleevec on BACE1 or an indirect effect through interaction with APP. Interestingly, it has been reported that a series of benzofuran-containing compounds selectively inhibit BACE processing of APP in vitro by binding directly to APP around the BACE cleavage site (17), and another study involving two flavonoid compounds reported similar results (18). It is unlikely that Gleevec inhibits BACE cleavage of APP by the same mechanism, however.…”
Section: Resultsmentioning
confidence: 69%
“…BACE inhibitor IV completely eliminated BACE1 cleavage of the APP-C140 substrate, in contrast to Gleevec, which had no effect at all concentrations tested, thus again ruling out a direct inhibitory effect of Gleevec on BACE1 or an indirect effect through interaction with APP. Interestingly, it has been reported that a series of benzofuran-containing compounds selectively inhibit BACE processing of APP in vitro by binding directly to APP around the BACE cleavage site (17), and another study involving two flavonoid compounds reported similar results (18). It is unlikely that Gleevec inhibits BACE cleavage of APP by the same mechanism, however.…”
Section: Resultsmentioning
confidence: 69%
“…Espeseth et al 11 describe an assay that is suitable for measuring β-secretase activity via measurement of sAPPβ. The same group also recently reported the development of assays that can measure sAPPα as well as genetically modified forms of Aβ peptides.…”
Section: Discussionmentioning
confidence: 99%
“…Also, among the 881 articles describing Biacore-based studies, 84% included information about which platform was used: most often studies were performed using the 3000 (38%), 2000 (22%), X (16%), and 1000 (4%) platforms, with the residual 4% using S51 [157,757,760,761,768,[779][780][781][782][783][789][790][791]798,918], Flexchip (formerly Applied Biosystems 8500 Affinity Analyzer) [138,338,434,435,583], Q [926,928,929,931,933,934,936,939,940], J [199,240,614,827,915], and Bialite [873].…”
Section: Overview Of Primary Research Articlesmentioning
confidence: 99%